1980
DOI: 10.1210/endo-107-5-1634
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Utilization in Relation to Insulin Secretion in NZO and C57B1 Mouse Islets*

Abstract: Further studies of insulin secretion from isolated pancreatic islets of the NZO strain of obese hyperglycemic mouse have shown markedly impaired insulin secretory responses to D-glucose in islets from fasted or fed mice. NZO islets at a low glucose concentration (3.3 mM) showed a significant insulin secretory response to 0.5 mM 3-isobutyl-1-methylxanthine (IBMX), a phosphodiesterase inhibitor, but in the presence of this agent showed no significant additional response to increased glucose concentration. This c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…In this regard, it also resembles the human condition. Previous studies on the NZO mouse have shown evidence for insulin resistance in skeletal muscle (17,21,22), white adipose tissue (17,21,23,24), and the liver (25) as well as defects in glucose-stimulated insulin secretion (15,16,(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it also resembles the human condition. Previous studies on the NZO mouse have shown evidence for insulin resistance in skeletal muscle (17,21,22), white adipose tissue (17,21,23,24), and the liver (25) as well as defects in glucose-stimulated insulin secretion (15,16,(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Glucose utilization was determined by measuring the formation of 3 (19,20). Islets were preincubated in KRB (as in the insulin secretion studies) for 30 min before groups of 10 islets were incubated in 40 l fresh KRB containing 20 mm glucose and 2 Ci …”
Section: Glucose Utilizationmentioning
confidence: 99%
“…This rodent has the typical hyperinsulinism and insulin resistance associated with obesity; blood glucose is mildly elevated, if at all. 60 Uniquely, it has a high incidence of autoimmune disorders, including circulating antibodies against tissue insulin receptors. 61 Glomerular nephritis from immune complexes is common.…”
Section: Obese Modelsmentioning
confidence: 99%